(untitled) (Vietnam Journal of Community Medicine, 2025)
Fascioliasis is a worrying parasitic disease that has a major impact on the livestock economy and human health worldwide. Objective: Evaluate changes in knowledge and attitudes about fascioliasis prevention among students at Tan Tao University after health education using Communication - Health Education videos. Methods: The study of helminth health education intervention on a group of subjects with a comparison before and after the intervention, was conducted on 153 students from 5 faculties studying at Tan Tao University from April to June 2024. Results: Before intervention, knowledge about the disease fascioliasis was achieved only reached 44.44%. After intervention, knowledge was significantly improved, reaching 76.47% (p < 0.001). Before intervention, the rate of positive attitudes was 70.59% and after intervention the rate increased to 84.97% (p < 0.05). Conclusions: Students’ knowledge and attitudes about fascioliasis prevention have improved significantly after health intervention education